Tahap amalan kepimpinan transformasional dalam kalangan pengetua sekolah menengah daerah Saratok, Sarawak - Dom Nambi, Sabai (2010)
The purpose of this study was to identify the level of transformational leadership as practiced by school principals in Saratok district secondary school on the idealized influence, individual consideration, intellectual stimulation and inspirational motivation aspects. The respondents consisted of 155 teachers from three school involved in the study. The instrument used to measure principal's transformational leadership practiced was "Multifactor Leadership Questionnaire" (MLQ). Alpha Cronbach reliability test value was .851. The data was analyzed with descriptive of percentage, mean, frequency, t-test and one way ANOVA analyses, through the Statistical Package for the Social Sciences (SPSS) version 15.0. The result showed that the principals of Saratok district secondary school practiced a medium level of transformational leadership in every dimension studied. The study also showed that teachers' perceptions by sex, age, teaching experience and race are not significantly related to principals's transformational leadership practiced.